Cardiac CT for the Interventional Cardiologist. Issue 1 (March 2016) - Jones, D. A.; Cospite, V.; Pugliese, F.
Abstract: Cardiac computed tomography (CT) is a rapidly evolving imaging modality that has developed quickly over the last decade, to establish itself as a robust non‐invasive method to assess coronary artery disease. Qualitative and quantitative assessment of atherosclerotic coronary stenosis with cardiac CT has been favorably compared with invasive coronary angiography and intravascular ultrasound (IVUS) and importantly may help improve risk stratification and predict prognosis. Cardiac CT can visualize coronary artery bypass grafts with high diagnostic accuracy, with the evaluation of stents improving all the time. Importantly for the interventional cardiologist, it has evolved into a crucial tool assisting in the planning of both coronary and structural heart interventions, with transcatheter aortic valve implantation the most successful example. With its resemblance to IVUS in the capability to assess both the lumen and vessel wall, cardiac CT provides additional information on the composition of the lesion and reference segments which might allow accurate selection of devices, potentially leading to complete lesion coverage, less incomplete stent apposition, and larger postprocedural diameters. An understanding of the uses of CT and keeping up to date with evolving CT technology is critical for the interventional cardiologist as the use of CT continues to evolve and establish itself as an everyday adjunct to cardiac intervention. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/4193301/Activity.aspx